High prevalence of Chlamydia trachomatis and Neisseria gonorrhoeae in Western French Guiana - Manca,Maria-Francesca (2020)
ABSTRACT The purpose of this study was to estimate the prevalence of Chlamydia trachomatis (CT) and Neisseria gonorrhoeae (NG) infections in western French Guiana and to analyze associated factors with both infections. A retrospective study was conducted in a sexually transmitted infections clinic in 2017. Women (n = 338) were tested by real-time polymerase chain reaction for vaginal, anal and throat CT and NG infections. Men (n = 192) were evaluated using urine specimens. Socio-demographic and sexual behaviour data were collected by nurses with a structured questionnaire. The prevalence of CT and NG infections among women were 24.3% and 13.3%, respectively, and 12.0% and 7.3% among men. Women aged under 25 years had a higher risk of CT and NG infections than women aged 35 years or more. Another risk factor for CT infection was low educational level, and occasional unprotected sex for NG infection. CT and NG infections were associated with reporting symptoms among men. Very high prevalences of CT and NG infections among women and men were found, which suggest that a large-scale screening strategy should be implemented in French Guiana.